Clinical and microscopic evaluation of extracapsular stabilisation technique for treatment of cranial cruciate ligament rupture in local dogs - Tahier, Abdullah (2021)
One of the most common orthopedic conditions and the cause of lameness in adult dogs is cranial cruciate ligament (CCL) rupture. The purpose of this study was to evaluate the clinical and histopathologic results of the extra capsular stabilization (lateral imbrication) technique (ECST) to treat CCL rupture using conventional thick surgical suture to stabilize the joint. Four (eight stifle, the right stifle is treatment and the left is control) adult medium size (13-18 kg) male dogs were used in this study. General physical examination and orthopedic examination are performed to all the subjects prior to the surgery. The selected dogs should be clinically sound and have no signs of muscular atrophy or other musculoskeletal problems. CCL rupture was experimentally induced, and these dogs (right leg) were surgically treated with ECST using Ethilon® size 1, but the left leg is control group we do not use any treatment. The clinical outcomes were evaluated by physical examination, radiology, postmortem and histopathological examination throughout and after 6 weeks following the surgery. The physical examination includes gait analysis and orthopedic examination. Postoperative data collection includes lameness at stance, walk and trot, Glasgow pain assessment, Gross joint swelling evaluation, tibial thrust test and anterior drawer test, were also performed. Score of 1 to 4 lameness was observed to the operated limb throughout 6 weeks post-surgery. However, radiological examination showed no obvious abnormality findings such as sclerosis or osteophytes within the 6 weeks period. Mild to moderate osteoarthritis was seen, however there was no obvious different in the presence of inflammatory cells between the operated and non-operated joint fluid. The joint swelling was not apparent despite the positive cranial drawer and tibial thrust test that suggested joint instability. There was also evidence of loosen and loss of suture integrity used to stabilize the joint upon post-mortem examination. Microscopically, the total increase of lateral articular thickness measurement in the treatment group was over 129 μm thicker than the control group and 21 μm increase seen in medial articular thickness as compared to the control group 6 weeks post-surgery. The caudal cruciate ligament integrity showed score 0 to 2 (showed preserved full thickness to fiber rupture damage) in the treatment group as compared to the control group (score 0 to 1: preserved full thickness to superficial fraying damage). The lateral meniscus in the treatment group showed a score of 1 to 3 lesions compared to the control that showed a score of 1 lesions. In addition, there was grade 1 to 2 lesion in the treatment group in compared with no lesions observed in the control group. The study highlighted some novelty in the findings, particularly the outcome of using Ethilon® size 1 suture in extracapsular stabilization surgery for cranial cruciate ligament rupture that was assessed clinnically and microscopically.